Clinical and electrophysiological characteristics of Guillain‐Barré syndrome in Colombia (2019)
Despite the wide literature describing the features of Guillain‐Barré syndrome (GBS) in different populations worldwide, Colombian data are very scarce. We aim to characterize patients with GBS in a general hospital setting in Colombia. We conducted a retrospective chart review of GBS cases managed at the Hospital Universitario Fundación Santa Fe de Bogotá, from 2011 to 2016. Twenty‐three patients were included. The most commonly reported symptoms were paresthesias (65%), pain (61%), proximal (22%) and distal (74%) limb weakness, and facial palsy (30%). 9% of patients had Fisher syndrome and 21% had other variants: Bickerstaff, pharyngeal‐cervical‐brachial pattern, and facial diplegia. There was a predominance of the demyelinating form (70%), with only 22% of patients presenting with the axonal variants. Our results are concordant with previous studies in Colombia.